Association between nutritional knowledge and body image with the risk of eating disorders among adolescent girls in Malang City - Galih Raditya Hendrato; Intan Yusuf Habibie; Agustiana Dwi Intiah Ventiyaningsih; Annisa Rizki Maulidiana; Dias Paramita; Novelyn Almareza (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Nutrient intake during adolescence plays an essential role in supporting optimal growth and development of the body. Eating disorders are common problems experienced by adolescent girls. Several factors may contribute to the occurrence of eating disorders, including the level of nutritional knowledge and body image perception. This study aimed to analyze the relationship between nutritional knowledge and body image and the risk of eating disorders among adolescent girls in Malang City. This study employed an analytical observational design with a cross-sectional approach. A total of 160 adolescent girls from five public vocational high schools in Malang City were selected using cluster sampling. The study will be conducted from August 2024 to January 2025. Nutrition knowledge was assessed using a 14-item questionnaire adapted from previous studies, body image was measured using the Body Shape Questionnaire (BSQ-34), and the risk of eating disorders was determined using the Eating Attitudes Test (EAT-26). Data were analyzed using the Spearman's correlation test. The results showed a significant correlation (p < 0.05) between nutrition knowledge (r = -0.292) and body image (r = 0.368) and the risk of eating disorders among adolescent girls in Malang City. These findings indicate that eating disorders among adolescent girls are influenced not only by nutritional aspects but also by psychological factors.